Changes in hematological status depending on reproductive stage of ewes naturally infected with internal parasites in North–Eastern Algeria - Hadef, Ahmed; Righi, Souad; Ghouar, Abdelbasset (SaberULA, 2023)
In Algeria, sheep farming is still largely traditional, and ewes are subject to various pathologies, particularly parasitic diseases leading to reproductive failure and production losses. To assess the influence of internal parasites (helminths and protozoa) and their interaction with the different phases of reproduction and season on hematological parameters, fecal and blood samples (n = 89) were taken from ewes during the period from the end of gestation to 3 months after parturition, two weeks apart. Animals were reared under a traditional pasture–based farming system in a Region of Northeastern Algeria characterized by a Mediterranean climate. Parasitic coproscopy results showed the consistent presence of digestive strongyles, Strongyloides, Trichuris ovis, Moniezia spp., Fasciola hepatica, and Coccidia. Hematological parameters, mainly hematocrit (HCT), hemoglobin (HGB), and erythrocytes (RBC), showed lower levels in anemic ewes throughout the study period. These hematological effects became significantly prevalent in 91% of the animals (P<0.05) during the third month postpartum (p.p.). The use of a mixed–effects model confirmed the significant hematological effect (P<0.05) of internal parasitism, which was amplified significantly by its interaction with the reproduction stage for HCT and RBC (P<0.01). Monitoring of blood biological constants in ewes during the critical reproductive stages seems to provide valuable data to improve their welfare and resistance to potential internal parasites.
Cambios en el estado hematológico en función de la fase reproductiva de ovejas infectadas naturalmente por parásitos internos en el noreste de Argelia
Keywords: Ovejas; Hematología; Parásitos internos; Periparto; Universidad del Zulia (LUZ); Universidad de Los Andes (ULA); Ewes; Hematology; Internal parasites; Peripartum; Revista Científica; Revista Científica: Artículos; Medio Ambiente; Revistas